2013
DOI: 10.1088/0031-9155/58/9/n135
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the energy-subtracted CT number to electron density based on a single linear relationship: an experimental verification using a clinical dual-source CT scanner

Abstract: In radiotherapy treatment planning, the conversion of the computed tomography (CT) number to electron density is one of the main processes that determine the accuracy of patient dose calculations. However, in general, the CT number and electron density of tissues cannot be interrelated using a simple one-to-one correspondence. This study aims to experimentally verify the clinical feasibility of an existing novel conversion method proposed by the author of this note, which converts the energy-subtracted CT numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…for Z eff calculation. Saito and his collaborators demonstrated in previous studies that ρ e can be computed by merely performing the weighted subtraction of high‐ and low‐energy CT images using a calibration phantom and a least‐squares fitting procedure to find the optimal weighting factor. This method yielded values of ρ e with an absolute error of less than 1% for calibration phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…for Z eff calculation. Saito and his collaborators demonstrated in previous studies that ρ e can be computed by merely performing the weighted subtraction of high‐ and low‐energy CT images using a calibration phantom and a least‐squares fitting procedure to find the optimal weighting factor. This method yielded values of ρ e with an absolute error of less than 1% for calibration phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that a clinical DECT scanner was able to extract Zeff, and density ρ of different tissue substitutes, next to ΔHU and ρe [7981]. This suggested that when a large quantity of high-density and high atomic number structures are in the planning field, DECT-derived calculations show accurate and reliable inhomogeneity corrections in RT treatment planning [82]. …”
Section: Applicationsmentioning
confidence: 99%
“…To extend the usable region of the ρ e calibration, we also included a homemade insert composed of an aluminum (Al) rod (99.999% purity) embedded in a urethane-resin pipe. 17 Figures 1(b) and 1(c) exemplify the SECT images of the body EDP and head EDP, respectively, as measured using the DSCT scanner at 120 kV. In order to investigate the impact of beam hardening on the reliability of the dose calculation, two different LUTs for the ρ e calibration were provided as inputs for a treatment planning system (TPS).…”
Section: C Electron Density Phantommentioning
confidence: 99%
“…The reliable linearity of the ∆HU-ρ e plot has been confirmed experimentally using clinical dual-source CT (DSCT) scanners with electron density phantoms (EDPs) by a number of investigators. [17][18][19] The main objective of this study is to present an initial implementation of the ∆HU-ρ e conversion method for the tissue inhomogeneity correction in radiotherapy treatment planning. This paper demonstrates two radiotherapy plans for an anthropomorphic phantom to compare the performance of the ∆HU-ρ e conversion with the conventional HU-ρ e conversion with regard to the reliability of dose calculations.…”
Section: Introductionmentioning
confidence: 99%